Zinc(II) and chloroindium(III) phthalocyanines bearing ethyl 7-oxy-6-chloro-4-methylcoumarin-3-propanoate groups: Synthesis, characterization and investigation of their photophysicochemical properties - (:unkn) unknown (WORLD SCI PUBL CO INC, 2018)
In this study, ethyl 7-hydroxy-6-chloro-4-methylcoumarin-3-propanoate (1), ethyl 7-(2,3-dicyanophenoxy)-6-chloro-4-methylcoumarin-3-propanoate (2), ethyl 7-(3,4-dicyanophenoxy)6- chloro-4-methylcoumarin-3-propanoate (3), ethyl 4-chloro-5-(7-oxy-6-chloro-4-methylcoumarin3- propanoate) phthalonitrile (4) were synthesized. The phthalonitrile derivatives (2, 3 and 4) were converted to their peripheral tetra, non-peripheral tetra and peripheral chlorocta substituted zinc(II) and chloroindium phthalocyanine derivatives. All novel compounds were characterized by elemental analysis, FT-IR, H-1-NMR, MALDI-TOF mass spectrometry and UV-vis spectral data. Additionally, the spectral, photophysical (fluorescence quantum yields and lifetimes) and photochemical (singlet oxygen generation and photodegradation under light irradiation) properties of the resulting substituted phthalocyaninatozinc(II) and indium(III) chloride complexes (5-10) were investigated in DMF, and the obtained results were compared for determination of the effects of the substituents' positions and the variety of the central metal atom on these properties. The fluorescence quenching behavior of these phthalocyanines (5-10) were also investigated using 1,4-benzoquinone as a quencher. The obtained ethyl 7-oxy-6-chloro-4-methylcoumarin-3-propanoate bearing phthalocyaninatozinc(II) (5, 7 and 9) and indium(III) chloride (6, 8 and 10) complexes showed excellent solubility in most organic solvents. They produced high singlet-oxygen and showed appropriate photodegradation which is very important for photodynamic therapy applications.
Keywords: phthalocyanines; coumarin; zinc; indium; fluorescence; photodegradation; singlet oxygen; COUMARIN; AGGREGATION; DERIVATIVES; PHOTOSENSITIZERS; PHOTOCHEMISTRY